Leaf Peroxidase, Malate Dehydrogenase and Esterase Isoenzyme Pattern in ten Sandal (Santalum album L.) Types Showing Variations in Leaf Pattern - Parthasarathi, K.; Rangaswamy, C. R.; Angadi, V. G. (Indian Forester, 1985)
A study of the isoenzyme pattern in respect of peroxidase malate dehydrogenase and estarase in the fully expanded green healthy leaves of different types of Sandal (Santalum album Linn.) plants showing variation in their leaf shape (ovate,lanceolate,linear and elliptic) has shown that (I) characteristic differences exist between the sandal leaf types in their pattern of isoenzymes of peroxidase and malate dehydrogenase at vegetative as well as flowering stages, (II) in the sandal plants with big ovate leaves, three sub-types exist, and (III) the sandal plants with normal ovate wavy and normal ovate non-wavy leaves are genetically very close.